Bio-jet fuel production from crude palm kernel oil under hydrogen-nitrogen atmosphere in a fixed-bed reactor by using Pt/C as catalyst - Worada Moonsrikaew; Nattee Akkarawatkhoosith; Tiprawee Tongtummachat; Amaraporn Kaewchada; Kun-Yi Andrew Lin; Rebrov Evgeny; Attasak Jaree (Energy Conversion and Management: X, 2023)
This research presents a study on the production of biojet fuel using crude palm kernel oil (CPKO) as a novel source. The aim of the research is to explore an efficient and high-throughput process for biojet production from CPKO. The experiment was conducted using a reactor packed with 5 wt% platinum on carbon (Pt/C). Several key operating variables, such as reaction temperature, hydrogen-to-nitrogen ratio, pressure, gas flow rate, and CPKO flow rate, were investigated to optimize the yield of liquid product and biojet fuel. The optimal conditions determined were a reaction temperature of 400 °C, pressure of 500 psi, CPKO flow rate of 0.02 mL/min, hydrogen-to-nitrogen ratio of 75:25, and gas flow rate of 25 mL/min. Under these conditions, the biojet fuel yield reached 59 %, with a productivity of 330.6 gproduct/gcat-h. The results demonstrated superior production performance compared to other existing processes in the field.